A relação entre unidades gestuais e quebras prosódicas: o caso da unidade informacional Parentético - Camila Antônio Barros (2021)
The research presented in this dissertation aimed to map gestures in the Parenthetical information unit. The research was based on the crucial role of action for speech and gesticulation, which, on the one hand, guides the frame of speech acts in speech (CRESTI, 2000) and, on the other hand, it organizes how spatio-motoric information is packaged (KITA; ÖZYÜREK, 2003). It is argued that, although qualitatively different, the multimodal linguistic production complies with the action underlying the speech acts. To conduct the study, a multimodal corpus was compiled, featuring 24 minutes total and about 4,000 words of monologic texts. The data were treated through software Praat (BOERSMA; WEERNIK, 2020) and ELAN (WITTENBURG et al., 2006) software; the former was used for the transcription, segmentation, and labeling of speech data and the latter for the annotation of units, phrases, and gestural phases, in addition to the parameters of handshape, position, orientation and type of movement (adapted from BRESSEM; LADEWIG; MÜLLER, 2013). Parentheticals, an information unit that provides a comment on its host unit (TUCCI, 2010), were qualitatively analyzed regarding the possibilities of gestural mapping. The analyzed data revealed that Parentheticals instantiate levels both in speech and in gesture; additionally, Parentheticals boundaries are characterized by an interruption in the gesture pattern in the utterance. The interruption may be marked by an opposition between a (partial) rest position and gesture or by shifts in movement, handshape, or gesture position. Different Parenthetical levels are also gesturally marked. Those possibilities reinforce the understanding of the Parenthetical informational unit as a level in speech that is separated from the hinc et nunc which inserts an information in the utterance. The results found also reinforce the theoretical assumptions that point to a functional synchrony between gestures and speech (McNEILL, 1992; KENDON, 2004; LOEHR, 2004), beyond the temporal synchronicity of their production, according to previous studies within the Language into Act Theory paradigm (CANTALINI, 2018; CANTALINI; MONEGLIA, 2020). Finally, more work is needed on both production and perception of gestural mappings in the Parenthetical unit. The main contributions of the work are the proposal of a simplified protocol for the compilation of multimodal data, and a qualitative analysis that looks at the gesture / speech interface in Parenthetical units in Brazilian Portuguese.